2023
DOI: 10.1002/acr.25019
|View full text |Cite
|
Sign up to set email alerts
|

Examining Rehabilitation Dose in Adults With Rheumatoid Arthritis: Association With Baseline Factors and Change in Clinical Outcomes

Abstract: Objective. To evaluate the association of baseline factors with rehabilitation dose and the association of rehabilitation dose with meaningful change in physical function, pain, and fatigue over 6 months among adults with rheumatoid arthritis (RA).Methods. Using data from the National Databank for Rheumatic Diseases registry, we extracted baseline characteristics and self-reported physical function (Health Assessment Questionnaire), pain (visual analog scale [VAS]), fatigue (VAS), rehabilitation dose (low: 1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…2,3 In this issue of The Journal of Rheumatology, Lane et al present their findings of a cross-sectional study of Medicare data showing disparities in PT utilization by SES and race and ethnicity among persons with RA. 4 Improvement in function with exercise and PT has been reported in RA, and a greater number of PT visits is also associated with greater functional improvement 5 ; however, as the authors point out, uptake of PT among persons with RA is low. 4 Non-Hispanic Black individuals with self-reported arthritis of any type had lower odds of a rehabilitation visit compared with White individuals, 6 but no large study of PT utilization among persons with RA has been reported.…”
mentioning
confidence: 98%
“…2,3 In this issue of The Journal of Rheumatology, Lane et al present their findings of a cross-sectional study of Medicare data showing disparities in PT utilization by SES and race and ethnicity among persons with RA. 4 Improvement in function with exercise and PT has been reported in RA, and a greater number of PT visits is also associated with greater functional improvement 5 ; however, as the authors point out, uptake of PT among persons with RA is low. 4 Non-Hispanic Black individuals with self-reported arthritis of any type had lower odds of a rehabilitation visit compared with White individuals, 6 but no large study of PT utilization among persons with RA has been reported.…”
mentioning
confidence: 98%